Measuring English Teachers' Digital Literacy in Applying ICT: A Study in a Secondary School - Siti Niah; Prih Febtiningsih; Najihah Mahmud (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The development of digital technology in education requires teachers to have adequate digital literacy to support effective and innovative English language learning. However, the digital competence of English teachers in secondary schools still shows inequality, especially in the pedagogical integration of ICT, digital assessment, and technology-based professional development. This study aims to analyze, evaluate, and interpret the level of digital literacy of English teachers in the application of ICT based on the Digital Competence for Language Teachers DC4LT framework. This study used a mixed methods method with an explanatory sequential design. The research subjects consisted of 36 secondary school English teachers, while the instrument trial subjects involved 15 teachers outside the research sample. Data collection was carried out through questionnaires, semi-structured interviews, and documentation using instruments in the form of a validated DC4LT questionnaire and interview guide. Quantitative data were analyzed using descriptive statistics, factor analysis, t-tests, Pearson correlation, and linear regression, while qualitative data were analyzed thematically. The results showed that teachers' digital competence was in the low to moderate category across all DC4LT dimensions, with digital content development as the highest aspect and professional development as the lowest aspect. The study's conclusions indicate that teachers' digital literacy is influenced by individual competency, institutional support, and the availability of digital infrastructure. The implications of this research emphasize the importance of ongoing training programs and contextual ICT integration policies in English language learning.